Zeroing the transfer matrix of the Roesser model of 2-D linear systems - Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
Controllability, observability and the transfer matrix of the discrete 2-D Roesser model are analyzed. It is shown that the controllability of the Roesser model is invariant under state feedbacks and the observability under output feedbacks. Sufficient conditions are established for the zeroing of the transfer matrix of the Roesser model.
Keywords: controllability; observability; 2-D Roesser model; state feedback; output feedback; zeroing of the transfer matrix